Effect of limited irrigation and planting systems on yield and water productivity of maize (Zea mays) - KAUR, RAMANJIT; KUMAR, SUNIL; MEENA, S L; DASS, ANCHAL; BANA, R S; SINGH, TEEKAM; KUMAR, SHITAL (The Indian Journal of Agricultural Sciences, 2024)
A field experiment was conducted during the rainy (kharif) seasons of 2019 and 2020 at the research farm opf ICAR-Indian Agricultural Research Institute, New Delhi to study the effect of limited irrigation application and planting systems on yield and water productivity of maize (Zea mays L.). The experiment was laid out in factorial randomized complete block design with 3 replications. The experiment consisted of two crop establishment methods as one factor, viz. Narrow bed planting and broad bad planting and 5 irrigation levels, viz. 25% DASM (Depletion of available soil moisture); 25% DASM at tasselling, silking, grain filling and 50% during rest of time; 50% DASM at all growth stages; 50% DASM + KCl spray at 40 DAS and at pre-tasselling; and 50% DASM+2% Urea spray at 40 DAS and at pre-tasselling. Experimental results revealed that the broad bed system of planting during 2019 and 2020 recoded significantly higher grain yields (4.37 and 4.57 t/ha) compared to the narrow bed system (4.23 and 4.38 t/ha), respectively. Regarding different irrigation levels, the highest water productivity (91.26 and 199.76 kg/ ha-cm) was observed with irrigation at 50% DASM along with two sprays of urea at 40 DAS during both the years, respectively. It was concluded that broad bed along with irrigation at 50% DASM with two sprays of urea proved to be most effective approach to enhance water productivity and yield of maize crop.